Identifikasi molekuler bakteri indigenous penghasil enzim amilase dari pati sagu asal Poom Kepulauan Yapen - Hesron; Massora, Maria; A. Mogea, Rina; Wanggai. I. M; Utami. P (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: This study aimed to identify indigenous bacterial isolates producing Amylase ezyme from sago starch from Poom, Yapen Islands, using the 16S rDNA sequence molecular method. The isolates identified were IA4 and IA8, which exhibited the highest values of assimilase enzyme activity. Bacteria were identified based on DNA amplification using Polymerase Chain Reaction (PCR) with primers 27F and 1492R. Based on the results of molecular identification, the similarity index of Isolate IA4 and Bacillus cereus D21 is 97.80%, while isolate IA8 had a similarity index of 99.79% with Alcaligenes faecalis Y5. Therefore, the amylolytic bacterial isolates were named Bacillus cereus strain IA4 and Alcaligenes faecalis strain IA8.